Effect of additives and powder preparation techniques on PTCR properties of barium titanate - Chatterjee, S.; Stojanovic, B. D.; Maiti, H. S. (Elsevier B.V., 2003)
PTCR barium titanate has been prepared following two different powder preparation techniques: the solid-state reaction route and co-precipitation route for the comparison of results. The co-precipitation route produces better PTCR characteristics with low room temperature resistivity and better reproducibility of prepared samples. The effects of different concentrations of additives like donors, acceptors and excess titanium have been optimized to get good quality PTCR samples. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: semiconducting barium titanate; PTCR effect; co-precipitation; solid-state reaction